Obesity Genetics - Hendi Wicaksono (Faculty of Medicine Universitas Kristen Duta Wacana, 2022)
Obesity is a health problem that become burden all over the world, andÂ affected all age groups. An increase in body weight above normal often characterises it. Genetic and environmental factors are known to be the main cause of obesity. Based on several studies, it turns out that genetic factors play a role of 40-60% in the incidence, however the role of genetic factors in obesity still not fully explained. The author wrote the topic of genetics and obesity based on his research experience regarding genotype polymorphisms associated with obesity. The aim of this book is to provide a new perspective on genetic factors as a causal factor and how genetics plays a role in obesity.